EXPERIENCES OF METH-DEPENDENT PATIENTS UNDERGOING CONTINGENCY MANAGEMENT (CM) THERAPY - Mohd Khairul Anuar Rahimi; Mohamad Salleh Abdul Ghani; Mohamad Isa Amat; Haslee Sharil Lim Abdullah; Norizatul Masturah Mohd Zaki, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This study explored the experiences of meth-dependent patients to gain insight on their thoughts and feelings on the Contingency Management (CM) intervention used during their three-month therapeutic session at a rehabilitation center in Dengkil, Malaysia. This basic qualitative research interviewed seven participants who had just finished undergoing the CM intervention process as the main therapeutic approach. The results indicate eight major themes from three research questions: (a) increased strength to turn their life around, (b) provide positive feelings, (c) application of knowledge, (d) reward as an afterthought, (e) realization of correcting past mistakes, (f) continuous encouragement to change, (g) more confidence in their ability to change, and (h) happy seeing positive rewards to their actions. Results of the study indicate that they found CM to be successful in their recovery process from meth dependence, especially in strengthening their intrinsic motivation. Patients also feel that the reward-based system used in CM has been beneficial in making them feel more happier and realizing the past mistakes that they have made.